Analysis of the relationship of public budget deficit on external debt in lraq with in the framework of joint integration of the period (1990 – 2016 ) - علوان, غفران حاتم; طالب, ريام علي (Journal of Economics and Administrative Sciences, 2019)
AbstractThe term public budget defects became nowadays a chronic, economical phenomenon, almost all the countries weather advanced or development country suffered from it, despite the different visions to economic schools of a thought to accept or reject the deficit in public budget but the prevailed opinion that is needed to rule the role of the state by reducing the public spending which led to continuous deficits in public budget and the consequent upon increase in government borrowing, increase taxes on income and wealth, thus weakening the in contrive for private investment which contributed to the increase of in flationary stagnation, it became a duty to state covered by the lack of financial sources local which become difficult to be equal to the continuous increase in public spending, is a funding problem the main problem faced by developing state especially lraq, what forced it to resort to external loans which are often controlled by complex political and economic conditions, hence it has focused on finding the estimation and analysis of relationship between the deficit in public budget and external debt during the period (1990-2016) as a result of the difficult circumstances experienced by Iraq during this period Iraq faced difficult circumstances during his period of time, the budget was crippled as a result to the continuous increase in public spending ,which resulted in an increase in external debt as a source of funding this deficit ,and in the framework of rating this relationship, the researcher has reached that there is a relationship equilibrium between the deficit in public budget and external debt.